2017
DOI: 10.1177/0267659117729889
|View full text |Cite
|
Sign up to set email alerts
|

Beta-thalassemia in the paediatric cardiac surgery setting - a case report and literature review

Abstract: Beta (β)-thalassemia is a blood disorder with an incidence of 1 in 100,000. This case report outlines a patient with β-thalassemia requiring cardiopulmonary bypass (CPB) and the measures taken to ensure an uneventful procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…It ultimately results in a lack of developed erythrocytes. Additionally, it has been demonstrated that compared to normal erythrocytes, β-thalassemic erythrocytes have a haemolysis percentage that is approximately 115% higher 2 . This is the cause of the anemia and hypoxia symptoms that thalassemic individuals experience 3 .…”
Section: Introductionmentioning
confidence: 99%
“…It ultimately results in a lack of developed erythrocytes. Additionally, it has been demonstrated that compared to normal erythrocytes, β-thalassemic erythrocytes have a haemolysis percentage that is approximately 115% higher 2 . This is the cause of the anemia and hypoxia symptoms that thalassemic individuals experience 3 .…”
Section: Introductionmentioning
confidence: 99%
“…1 In children, are there new methods mandating a re-evaluation for blood conservation, allowing bloodless surgery in children, 2 should modified ultrafiltration be used in congenital heart disease 3 or how do we best care for those with a blood disorder that reduces the production of hemoglobin, such as beta-thalassemia? 4 How is temperature managed in different parts of the world? 5 Unique case studies can be the gateway for additional study: epoprostenol for treating oxygenator pressure drop, 6 bivalirudin use in a patient with heparin-induced thrombocytopenia in renal failure.…”
mentioning
confidence: 99%